TRIGONOMETRY SIMULATION LEARNING USING SCILAB BUDI DARMA UNIVERSITY - Siti Nurhabibah Hutagalung; Melda Panjaitan (Jurnal Mantik, 2022)
The research in this case aims to analyze learning in the form of simulations that can provide explanations and shape the character of the independence of Budi Darma University students to understand trigonometry material which so far has memorized the concept of formulas without knowing where it came from and the display form of the calculation results of basic concepts, graph functions and Pythagoreans and trigonometric angle ratio. The research stages consist of theoretical analysis, formulation of trigonometry, determination of input variables, program code input, simulation of display results and comparative analysis between theory and the resulting program simulation. The formation of trigonometric simulation concepts can be applied to learning in the fields of computers, engineering and everyday life.